Pengaruh Budaya Organisasi Terhadap Prestasi Kerja Karyawan Bagian Corporate Administrasion pada PT. NITTOH Presisi Indonesia - Ismulyana Djan; Siti Hindun (Jurnal Ilmiah Binaniaga, 2007)
The evaluation of performance is one of the important tasks done by a manager or a leader. In evaluating employees’ performance like and dislike is one factor that should be avoided by an evaluator to maintain the objectivity of the evaluation. The evaluation is necessary because it can be used to improve decision concerning personnel or to give feedback regarding the employees’ performance. There are two variables that can influence performance the first one is individual variable including attitude, characteristics, interests and motivation, experience, age, sex, education and other factors. The second one is situational variable that consists of physical and work factor, types of training and evaluation, wage system and social environment. Thus, it can be concluded that organization culture and employee’s performance are interdependent factors. The importance of organization culture in the organization life will increase employees’ performance. The organization culture that is employed at PT. Nittoh Presisi Indonesia are: Seiri (orderly), Seiton (neatness), Seiso (cleanliness), Seiketsu (eternal) and Sitshuke (discipline). The criteria in evaluating employee’s performance at PT Nittoh Presisi Indonesia among other things are: attendance sheet, obeying company’s rules, understanding of order, work diligence, partnership among colleagues, the quantity of target goal, the quality of the target work and capability and potential development. From ANOVA results on experiment variables it was found that F counted was 62.966 while the value of F table with degree of freedom (df = 2 and 56) on the α = 0.005 was 2.80. Therefore, since the value of F counted is bigger than F table (62.966 > 2.80), it can be concluded that the organization culture influences the employee’s performance at PT Nittoh Presisi Indonesia.